Protection against mobbing in work under non-employment contracts/non-labour employment contracts - Dzięgo, Beata (The use of atypical forms of employment in violation of labour and social security laws - diagnosis and prospects for the future, 2023)
Raising popularity of atypical forms of employment begs the question of applying standard regulations to them, such as the protection of worker’s rights, job security. One of the aspects is the use of regulations of mobbing and whether it can be used when it comes to other forms of employment. Character of this institution allows it to be used only in typical form of employment, which does not deprive others of the protection of their rights. It is possible to assert claims based violation on values protected by law, such as dignity or health. The legal definition of mobbing can be used as help to understand the situation of the individual and recognise the violation of one’s rights.